Neuropsychological alterations and neuroradiological findings in patients with post-traumatic concussion: results of a pilot study - A. Rădoi; M.A. Poca; V. Cañas; J.M. Cevallos; L. Membrado; M.C. Saavedra; M. Vidal; F. Martínez-Ricarte; J. Sahuquillo (Neurología (English Edition), 2018)
Introduction: Mild traumatic brain injury brain injury (mTBI) has traditionally been considered to cause no significant brain damage since symptoms spontaneously remit after a few days. However, this idea is facing increasing scrutiny. The purpose of this study is to demonstrate the presence of early cognitive alterations in a series of patients with mTBI and to link these findings to different markers of brain damage. Methods: We conducted a prospective study of a consecutive series of patients with mTBI who were evaluated over a 12-month period. Forty-one (3.7%) of the 1144 included patients had experienced a concussion. Patients underwent a routine clinical evaluation and a brain computed tomography (CT) scan and were also administered a standardised test for post-concussion symptoms within the first 24 h of mTBI and also 1-2 weeks later. The second assessment also included a neuropsychological test battery. The results of these studies were compared to those of a control group of 28 healthy volunteers with similar characteristics. Twenty patients underwent a magnetic resonance imaging (MRI) scan. Results: Verbal memory and learning were the cognitive functions most affected by mTBI. Seven out of the 20 patients with normal CT findings displayed structural alterations on MR images, which were compatible with diffuse axonal injury in two cases. Conclusions: Results from this pilot study suggest that early cognitive alterations and structural brain lesions affect a considerable percentage of patients with post-concussion syndrome following mTBI. Resumen: Introducción: Los traumatismos craneoencefálicos leves (TCE-L) han sido tradicionalmente considerados acontecimientos sin repercusiones cerebrales significativas, cuya sintomatología remite espontáneamente en unos días. Sin embargo, estos hechos son cada vez más cuestionados. Este estudio pretende objetivar la existencia de alteraciones cognitivas precoces en una serie de pacientes con TCE-L y relacionar los hallazgos con distintos marcadores de lesión cerebral. Métodos: Estudio prospectivo de una cohorte de pacientes con un TCE-L valorados de forma consecutiva durante 12 meses. De un total de 1.144 pacientes, se seleccionó a 41 (3,7%) que habían presentado una conmoción cerebral. Además de la valoración clínica habitual y de la práctica de una tomografía computarizada (TC) cerebral, los pacientes fueron estudiados mediante un test estandarizado para síntomas posconmocionales en las primeras 24 h después del TCE-L y al cabo de 1-2 semanas y, coincidiendo con la segunda valoración, mediante una batería neuropsicológica. Los resultados se compararon con los de un grupo de 28 voluntarios sanos de características parecidas. En 20 pacientes se practicó una resonancia magnética (RM) craneal. Resultados: En este análisis exploratorio, la memoria y el aprendizaje verbal fueron las funciones cognitivas más afectadas después del TCE-L. Siete de los 20 pacientes con TC cerebral normal presentaron alteraciones estructurales visibles por RM, que en dos casos fueron compatibles con la presencia de lesión axonal difusa. Conclusiones: Los resultados de este estudio piloto sugieren la presencia de alteraciones cognitivas precoces y lesiones cerebrales estructurales en un porcentaje no despreciable de pacientes que han presentado una conmoción cerebral recuperada después de un TCE-L. Keywords: Mild traumatic brain injury, Neuropsychological alterations, Diffuse axonal injury, Sport Concussion Assessment Tool 2, Susceptibility-weighted imaging, Post-concussion syndrome, Palabras clave: Traumatismo craneoencefálico leve, Déficits neuropsicológicos, Lesión axonal difusa, Sport Concussion Assessment Tool 2, Susceptibility weighted imaging, Síndrome posconmocional